PROFIL HUTAN PEGUNUNGAN KAMOJANG, JAWA BARAT - Isoralla, .; Djohan, Tjut Sugandawaty; Maulidika, Alicya Inmas; Agung, Putry (Universitas Pakuan, 2025)
This research was aims to study natural and disturbed mountain forest profile of Kamojang at 1300-1600 m dpl, West Java. Forest profile was made by Oldeman method, data were collected by quadrat plots size 20m x 20m with 4 times replicated. The result showed natural forest composed by 5 strata, disturbed forest composed by 3-4 strata without first strata. The most abundance trees in first strata was Castanopsis javanica between 2-11 ind/0,16 ha and in second strata was Engelhardia spicata between 5-7 ind/0,16 ha. All these locations study were not found any emergent trees and composed by different vegetation because of selective cutting activity to vegetation that had economic value. The most abundance growthform in natural and disturbed forest were sapling between 15-32 species/0,16 ha in natural forest and 3-23 species/0,16 ha in disturbed forest. The most abundance trees and sapling in natural forest were Villebrunea rubescens between 5-51 ind/0,16 ha. In contrast, most abundance trees in disturbed forest were Altingia excelsa 20 ind/0,16 ha and sapling were Erythtroxylum cuneatum between 1-19 ind/0,16 ha. There were variation presence of trees-seedling in natural forest, the most abundance were Morinda tomentosa between 1-26 ind/0,16 ha. The most abundance trees-seedling in disturbed forest were Dysoxylum parasiticum, Hypobathrum racemosum, Laportea sp., dan Macaranga rhizinoides between 3 ind/0,16 ha in Raksamala rehabilitated forest which growth naturally. Cover of canopy in natural forest were 0,17-0,32 ha/0,16 ha. In contrast, there were 0,02-0,08 ha/0,16 ha in disturbed forest. Nutrients content of soil such as NO3, NH4, PO4, K+, C, and BO in all locations were high. Content of nitrate around 10-60 ppm. Natural forest had interlock canopy and quilted layers which good for water conservatories. Both natural and disturbed forest were found invasive species Eupatorium odoratum. The limiting factor were the light and human activity.